(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The article features the system of three partial differential equations, which describes the stream stationary axial - a symmetric incompressible liquid in a pipe. The developed technique allows reduce the system of PDE to the difference equations which have been solved due to the grid method. Using computer program MAPLE different values of pressure’s difference in the following cases were calculated: a) a smooth pipe; b) the liquid is poured in inside a pipe through the reduced part o f a pipe; c) the liquid is poured in inside a pipe through a ring. The liquid’s flux modeling in a pipe is investigated at different values of parameter Re (Reynolds number), T (parameter of rotation) and A (whirlwind’s intensity). The considered technique is applicable in specific targets and processes of formation of whirlwinds, for example, a stream o f a liquid or gas in pipelines, in automobile mufflers, etc.